Effects of E-Cigarette Vapor Smoke on Pulmonary Alveoli in Rattus norvegicus Lungs - Edward Pandu Wiriansya; Dewi Rahman; Muhammad Naufal Zuhair; Syamsu Rijal; Dzul Ikram; Utomo Andi Pangnguriseng (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Vapor is considered a safer alternative to tobacco cigarettes because the high nicotine content is less. However, vapor still contains substances that are classified as toxic to humans. Short-term exposure to vapors from liquids can induce an inflammatory response in the lungs and cause oxidative stress. This study aimed to determine the effects of e-cigarette vapor smoke on pulmonary alveoli in Rattus norvegicus lungs. Methods: This was an experimental study on 32 adult male Rattus norvegicus rats. They were divided into two groups exposed to nicotine-containing vapor smoke two times a day for one and three months, respectively, and one group as control. After vapor exposure, the lung tissues of the rats were taken and then subjected to histopathological examination under a microscope. Results: After exposure for one month, epithelial and endothelial cells degenerated, characterized by a decrease in collagen and elastin fibers in the extracellular matrix. For three months, there were changes, the alveolar membrane had no nucleus, the surrounding endothelial cells were not visible due to damage to the extracellular matrix, the alveolar lumen had widened, causing edema in the lumen of the alveoli, and the alveoli wall was destroyed. Therefore, the connection between the alveoli was stretched. Conclusion: This study found that short-term exposure to nicotine vapor causes damage to the alveoli membrane.